Labor epidural analgesia onset time and subsequent analgesic requirements: a prospective observational single-center cohort study. (November 2019) - Nevo, A.; Aptekman, B.; Goren, O.; Matot, I.; Weiniger, C.F.
Highlights: Labor epidural analgesia (LEA) onset time may predict pain later in labor. There was a significant correlation between onset time and pain intensity at 60 min. Women with more pain at 60 min also had more pain at 120 min. Women with more pain at 60 min required more local anesthetic during labor. Abstract: Background: We investigated the correlation between lumbar epidural analgesia onset time and pain intensity at 60 and 120 min after initiation. Methods: We conducted a prospective observational study of nulliparous women receiving lumbar epidural analgesia (initial bolus 15 mL bupivacaine 0.1% with fentanyl 3.33 μg/mL), followed by patient-controlled epidural analgesia (PCEA). The measured variable was lumbar epidural analgesia onset time (time to pain numerical rating score ≤3). Secondary outcomes were pain score at 60 and 120 min and at full dilatation; and analgesic requirements through the labor. Results: One-hundred-and-five women were eligible for analysis. There was a significant correlation between lumbar epidural analgesia onset time and pain intensity at 60 min (Spearman's R 2 =0.286, P =0.003), but not at 120 min ( R 2 =0.030, P =0.76). Women who requested more PCEA boluses during the first 120 min had a longer lumbar epidural analgesia onset time ( R 2 =0.321, P =0.001) and reported higher pain scores at 60 min ( R 2 =0.588, P  <0.001) and at 120 min ( R 2 =0.539, P  <0.001). Women who reported higher pain scores at 60 min had more pain at 120 min ( R 2 =0.47, P  <0.001) and higher analgesic consumption during labor ( R 2 =0.403, P  <0.001). Women who were at a greater cervical dilatation at 60 and 120 min had higher pain scores at the same time point ( R 2 =0.259, P =0.008 and R 2 =0.243, P =0.013 respectively). Conclusion: There was a correlation between the onset time of lumbar epidural analgesia during labor and the pain score 60 min later but this had disappeared by 120 min.